Practical considerations of clinical XR (AR/VR) deployments - Morgan, Joseph W.; Patel, Rahul A.; Campbell, Scott (Frontiers in Virtual Reality, 2025)
Extended Reality (XR), which includes both Augmented Reality (AR) and Virtual Reality (VR), shows great promise in healthcare, with applications ranging from surgical simulations to patient rehabilitation and education. To ensure successful deployment, it is essential to address a wide range of different challenges, including those related to clinical efficacy, safety, ethics, technical requirements, institutional demands, provider and hardware considerations, as well as regulatory and reimbursement issues, all within the broader context of the healthcare system. Artificial intelligence, monopolistic payers, and the lack of a clear boundary between the consumer and healthcare spaces all represent both new challenges as well as opportunities. To fully harness XR’s potential, collaboration among technologists, clinicians, and policymakers is essential, ensuring the technology enhances patient care and education while maintaining safety and effectiveness.